2020
DOI: 10.1093/cid/ciaa1014
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Cardiovascular Events in Patients Infected With Human Immunodeficiency Virus and Hepatitis C Virus

Abstract: Background An increased risk of cardiovascular disease (CVD) was reported in patients coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV), without identifying factors associated with atherosclerotic CVD (ASCVD) events. Methods HIV–HCV coinfected patients were enrolled in the ANRS CO13 HEPAVIH nationwide cohort. Primary outcome was total ASCVD events. Secondary outcomes were coronary and/or cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
(86 reference statements)
1
11
1
Order By: Relevance
“…In this study we identified total cholesterol > 5.0 mmol/L as the only factor associated with an increased risk of ischaemic events. High total cholesterol has been identified as a risk factor for ischaemic events in HCV‐infected participants [37,38]. Previous studies also identified LDL cholesterol as a factor associated with the risk of ischaemic events [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we identified total cholesterol > 5.0 mmol/L as the only factor associated with an increased risk of ischaemic events. High total cholesterol has been identified as a risk factor for ischaemic events in HCV‐infected participants [37,38]. Previous studies also identified LDL cholesterol as a factor associated with the risk of ischaemic events [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…High total cholesterol has been identified as a risk factor for ischaemic events in HCV-infected participants [37,38]. Previous studies also identified LDL cholesterol as a factor associated with the risk of ischaemic events [37,38]. Participants with LDL cholesterol > 1.4 mmol/L had increased incidence rates [9.1 (4.9-16.9)] compared with participants with lower values [1.9 (0.3-13.2)].…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
“…It was shown that a total of 5,320 studies were obtained after literature search in the Medline, the Embase, and the Web of Science databases after excluding of the duplicated records, while 504 of them were excluded based on the titles and abstracts primarily because they were irrelevant studies. Then, 16 of the 28 potentially relevant studies were further excluded based on full-text review according to the reasons listed in Figure 1 and the other 12 studies were finally included (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Literature Searchmentioning
confidence: 99%
“…However, studies evaluating the influence of statin therapy on the risk of CV events, cancer, and all-cause mortality in PLWH showed inconsistent results (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Some studies suggested the benefits of statins on the above outcomes (22,25,30,31), while other studies did not suggest any benefits of statins (21,23,24,(26)(27)(28)(29)32). Therefore, we performed a meta-analysis to systematically evaluate the efficacy of statin on the risk of CV events, cancer, and all-cause mortality in PLWH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation